Death-related expressions in Javanese angkating layon speech and English eulogy - Munandar, Aris (Universitas Pendidikan Indonesia, 2019)
Cultures hold different perceptions of death and demonstrate different linguistic behaviors when performing funeral rituals. This article compares angkating layon speech in Javanese society and eulogies in American society focusing on the use of death-related expressions to reveal their rhetorical function and significance in articulating the two societies’ perception toward death. The data are collected from ten angkating layon speech texts recorded from actual funeral ceremonies and ten eulogy texts downloaded from the internet. Conceptually, this article applies Kunkel's and Dennis's (2003) idea of eulogical rhetoric and Lakoff's andJohnson's (1980) theory of conceptual metaphor. The findings show that both societies conceptualize death into DEATH IS A JOURNEY and DEATH IS REST. Angkating layon speech is an allusion for sincere acceptance of death, uses less elaborate positive euphemism as a brief report of the deceased’s good characters, and evokes empathy and sincere prayer for the deceased. Meanwhile, a eulogy is a means of maintaining togetherness between the dead and the living, uses elaborate positive euphemism to create a good impression of the eulogized, and thus, appeals more strongly to the memory of the living. It concludes that the Javanese are open about the dead body, create such euphemisms as almarhum(ah), layon/jenazah, and swargito mark the dead as 'other' suggesting that he/she is no longer part of the society, and readily accept a permanent separation from the dead. On the contrary, Americans are reluctant to mention the dead body, deny separation from the dead, and use almost non-existent lexical marker 'late' signifying death as another episode of life that never affects their relationship with the deceased.